Perancangan dan Implementasi Aplikasi Verifikasi SNMPTN di Universitas Andalas Berbasis Android dan PHP MYSQL - Deddy Prayama -; Yuli Resmawati - (Jurnal Ilmiah Poli Rekayasa, 2016)
Verification of entri exam as SNMPTN is an activity to confirm the data in schools which have been registered before at the University of Andalas. At the time of verification, the verification team still carries the paper to verify the data. Where as in times those are now many applications can facilitate the users. So to create verification application to facilitate the verification team to input data - verification of data and can be sent directly from the results of the verification data into the application server. This application only accessible for the verifier team, because this application an account to access it. Andalas University entri exam verification applications will be built using the Android programming language, PHP and MySql.